Diverging effects of tumor necrosis factor inhibitors and conventional synthetic disease-modifying antirheumatic drugs on immunosenescence and inflammageing in rheumatoid arthritis: a cross-sectional analysis - Tobias Schwarz; Giovanni Almanzar; Sebastian Völkl; Martin Feuchtenberger; Johannes Leierer; Christian Schmidt; Frank Deininger; Hans-Peter Tony; Marc Schmalzing; Martina Prelog (Immunity & Ageing)
Abstract Background Immunosenescence is characterized by a decline in naive T cells, a reduced T cell receptor repertoire, and the accumulation of terminally-differentiated and unspecifically-activated proinflammatory cells, a process called inflammageing. Premature immunosenescence is thought to be pathogenetically relevant in rheumatoid arthritis (RA), either by posing a risk factor for its development, or by advancing the rheumatic disease as a result of excess antigenic and inflammatory stimulation. We investigated parameters of immunosenescence in RA patients treated with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) only compared to patients treated additionally or exclusively with a tumor necrosis factor inhibitor (TNFi) and age-matched healthy controls to investigate the effect of RA treatment on age-associated T cell phenotypes and functions. Results The csDMARD-only treated patients, compared to the TNFi-treated patients and healthy controls, displayed an enhanced age-dependent decline in CD31+ recent thymic emigrants (RTE) and Interleukin-7 (IL-7)-receptor α-chain (CD127)-expressing CD4+ T cells participating in IL-7-associated homeostatic proliferation, a diminished proliferation of RTE and CD127+ T cells, as well as reduced T cell receptor excision circle (TREC) counts. However, whereas the RA patients exhibited reduced proportions of unspecifically activated IFNγ- and IL-17-producing T cells, TNFi initiation induced an increase in these proinflammatory cells. Conclusions Whereas a TNFi treatment seems to counteract the non-inflammatory aspects of immunosenescence, it induces increasing proportions of terminally-differentiated, cytokine-producing effector memory T cells, requiring awareness as possibly contributing to secondary autoimmune phenomena in RA.